The Search for a Landfill Site in an Age of Uncertainty: The Role of Trust, Risk, and the Environment - Ali, Harris Syed (My University, 1996)
This study investigates the explanatory power of the theory of reflexive modernization proposed by Anthony Giddens and the theory of the risk society proposed by Ulrich Beck by empirically examining the interactions and issues raised in the innovative, open, and, inclusive Guelph Landfill Search Process (GLSP). The notions of risk, trust, and the environment are central elements of these theories, both of which propose that social change in the contemporary era has been stimulated by a process of confrontation with modem environmental risks. As such, we have examined the role that these three factors played in the GLSP.
It was observed that despite efforts by the City to inculcate feelings of trust and confidence in the search process, a lack of trust still remained. It is argued that this lack of confidence was not due purely to political factors, but was also due to the lack of trust in the institution of science and technology in general. It was found that the notion of risk was central to accounting for the adoption of such a perspective.
A central factor in the treatment of risk was the lay awareness of the technical uncertainties inherent to environmental impact science. In the context of the GLSP, this lay awareness pertained to issues related to the uncertainty in determining the character of the waste stream, the uncertainty about the hydrogeological features of the potential sites, and the awareness of the limitations of the technical methods and technologies used to detect, monitor, and contain the toxic leachate generated from the proposed landfill.
Keywords: Sociology; Sociology